Digital Subtraction Angiography Contrast Material Transport as a Direct Assessment for Blood Perfusion of Middle Cerebral Artery Stenosis - Lu, Yun-Hao; Cai, Yan; Zhang, Yi; Wang, Rui; Li, Zhi-Yong (Frontiers in Physiology, 2021)
Digital subtraction angiography (DSA) is a fluoroscopic technique used extensively in interventional radiology for visualizing blood vessels. It has also been used to evaluate blood perfusion. However, the perfusion obtained in previous techniques was extracted from signal intensity rather than by the transport of contrast material (CM) through blood flow. The main aim of this study is to evaluate the morphological effects on the hemodynamics and the CM concentration in the middle cerebral artery (MCA) stenosis. We proposed a quantitative parameter, contrast material remaining time (CMRT), to describe the variation in CM transport over time. Computational fluid dynamics (CFD) simulations were performed on both the reconstructive synthetic models and the patient-derived models. In the synthetic models, we evaluated the variation of flow patterns and CM transport with different degrees of stenosis and the location of lesion. It was found that an increase in the degree of stenosis (from 30% to 80%) resulted in a significant increase of CMRT at the anterior cerebral artery (ACA) outlet (p=0.0238) and a significant decrease of CMRT at MCA outlet (p=0.012). The patient-derived models were reconstructed from pre- and post-interventional DSA images of a patient with MCA stenosis. Both blood flow velocity and CMRT increased at the ACA outlet but decreased at the MCA outlet. The perfusion analysis demonstrated that the perfusion function was improved after interventional surgery. In conclusion, changes in stenotic degree at MCA may lead to apparent differences in hemodynamic distribution and CM transport. CMRT could be a quantitative indicator to evaluate the changes in blood perfusion after intervention for MCA stenosis.